Program pembudayaan literasi dan teknologi maklumat : Persatuan Pustakawan Malaysia 2011/2012 - Mohd Yussof, Hashimah; Sujak, Kamal; Baharuddin, Mohammad Fazli; Mohamad, Ahmad Nadzri; Badrol Hisham, Syazwan Fikri; Mohd Amin, Zahari; Mohamed, Shaharom Nizam; Mohd Saad, Mohd Sharif (Persatuan Pustakawan Malaysia, 2012)
The Librarians Association of Malaysia in cooperation with Perbadanan Perpustakaan Awam Terengganu (PPAT), Perbadanan Perpustakaan Awam Negeri Sembilan (PPANS), Perbadanan Perpustakaan Awam Negeri Melaka (PERPUSTAM) and Kuala Selangor District Education Office with support from the Faculty of Information Management, Universiti Teknologi MARA (UiTM) through funds from the Malaysian Ministry of Information, Communication and Culture, Permodalan Nasional Malaysia and Telekom Malaysia (TM) organised the Culturalisation of Information Literacy and Technology Programme throughout 2011 dan 2012. The programme used a learning module that covers five aspects which focused on developing information literacy among students to equip them with the knowledge for recognising the need, searching, evaluating and using authoritative and useful information throughout their learning process.